2014
DOI: 10.4103/1305-7456.130605
|View full text |Cite
|
Sign up to set email alerts
|

Dental patient's knowledge and perceptions about the effects of smoking and role of dentists in smoking cessation activities

Abstract: Objectives:The objective of the following study is to assess the knowledge of patients about the consequences of smoking on the general and oral health, to analyze the patient's perceptions about the role of dentists in smoking prevention, counseling and cessation and to analyze the willingness of smokers to quit smoking following dentist's advice.Materials and Methods:A descriptive study was conducted in a sample of 486 dental patients visiting Vokkaligara Sangha Dental College and Hospital, Bengaluruin the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 24 publications
1
28
0
3
Order By: Relevance
“…In a Study done by Chanchal Gangwar et al [8], only 40% health workers had knowledge about tobacco causes oral cancer. Study done by Sood P et al [9] contradicted this statement in which majority of the subjects (80%) had knowledge that tobacco causes oral cancer. More than 80% of the health workers had knowledge that sugar causes dental caries which is contradicted by the study done by M Aggnur et al [10] in which they showed that 62.2% HCW's knew that sugar causes dental caries respectively.…”
Section: Discussionmentioning
confidence: 93%
“…In a Study done by Chanchal Gangwar et al [8], only 40% health workers had knowledge about tobacco causes oral cancer. Study done by Sood P et al [9] contradicted this statement in which majority of the subjects (80%) had knowledge that tobacco causes oral cancer. More than 80% of the health workers had knowledge that sugar causes dental caries which is contradicted by the study done by M Aggnur et al [10] in which they showed that 62.2% HCW's knew that sugar causes dental caries respectively.…”
Section: Discussionmentioning
confidence: 93%
“…By implication, the real situation in KSA could be worse than the already appalling picture. In the current study, the awareness among patients about the oral cancer was good in comparison with the previous studies (Al-Shammari et al, 2006;Sood et al, 2014;Terrades et al, 2009). However, statistically, many more patients will be affected by periodontal diseases than oral cancer.…”
Section: Discussionmentioning
confidence: 55%
“…In fact, several studies have already referred that patients considered tobacco cessation counseling by dentists to be favorable. 22,23 Furthermore, if adapted to dentistry, algorithms become instructive and easy to apply by the dentist, summarizing the primary steps in this type of intervention. 1 This study was also aimed to identify obstacles or barriers to the application of tobacco prevention and cessation interventions.…”
Section: Discussionmentioning
confidence: 99%